2015
DOI: 10.1089/apc.2015.0113
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Analysis of Risk Factors for Acquiring HIV Among Men Who Have Sex with Men: Implications for Implementing Pre-Exposure Prophylaxis Programs

Abstract: Current Centers for Disease Control and Prevention (CDC) guidelines for prescribing pre-exposure prophylaxis (PrEP) to prevent HIV transmission are broad. In order to better characterize groups who may benefit most from PrEP, we reviewed demographics, behaviors, and clinical outcomes for individuals presenting to a publicly-funded sexually transmitted diseases (STD) clinic in Providence, Rhode Island, from 2012 to 2014. Latent class analysis (LCA) was used to identify subgroups of men who have sex with men (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…In line with research in other in North and South American populations, 3,4,6,26-28,30 our findings suggest that HIV risk behaviors represent heterogeneous classes within a population. Participants who were younger, reported higher alcohol use, were married, and had low income were at higher risk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with research in other in North and South American populations, 3,4,6,26-28,30 our findings suggest that HIV risk behaviors represent heterogeneous classes within a population. Participants who were younger, reported higher alcohol use, were married, and had low income were at higher risk.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in other countries identified types of HIV risk behaviors in IDU and illegal opioid users, 3,26-29 heroin and cocaine users, 30 men who have sex with men, 4 and in a group of heterosexual and marginalized men in Peru. 6 In line with these studies, the current study provides a person-centered approach, using latent class analysis 31 (LCA), to analyze the spectrum of HIV risk behaviors for identifying groups of individuals who share similar HIV risk characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…21 CDC guidelines recommend considering PrEP in MSM who report condomless anal sex with men. 19 To promote PrEP among MSM, PrEP education and counseling were integrated into standard care at our STD clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The US-Food and Drug Administration approved Truvada as an oral PrEP treatment for MSM in 2012. 5 PrEP could help reduce HIV incidence among MSM, 6 who account for approximately two-thirds of new HIV infections in the United States. 7 Black MSM (BMSM) have the highest HIV incidence rates in the United States; reduction of such disparities is a vital part of the US National HIV/AIDS strategy.…”
mentioning
confidence: 99%